Baluran Nasional Park Savanna (Biodiversitas Journal of Biological Diversity, 2016)
One of the biodiversity richness in Indonesia is ecosystem of Baluran National Park savanna. This type of savanna is similar to African savanna that is included in tropical savanna. There are two types of savanna, namely flat and undulating savanna. The savanna ecosystem that covers about 40% of the total area of Baluran National Park has important role on supporting herbivore animals such as wild cattle (Bos javanicus), deer (Cervus timorensis) and wild buffalo (Bubalus bubalis). The variety of grasses and other vegetation provide food for those animals, therefore, the reduction of the reduction of quality and quantity of the savanna would reduce in the population of the herbivores. The savanna in the Baluran National Park is about 10.000 ha, however, due to invasion of Acacia nilotica has resulted in the reduction of the savanna reaching about 50%. Moreover, illegal grassing inside the Park has brought negative impact to the quality of the area and the wild fauna. Overgrazing may influence on the reduction of the population of wild fauna. Pressure to the savanna has a great impact on the balance and preservation of whole ecosystem in Baluran. Efforts have been made in order to restore the Baluran ecosystem such as preventing the expansion of A. nilotica as well as preventing illegal grazing. The Baluran National Park is still looking for the most effective and efficient way of preserving savanna ecosystem in Baluran.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKeywords: Baluran National Park, savanna, Acacia nilotica